2005
DOI: 10.1074/jbc.m413788200
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid-binding Protein, aP2, Coordinates Macrophage Cholesterol Trafficking and Inflammatory Activity

Abstract: Fatty acid-binding proteins are cytosolic fatty acid chaperones, and the adipocyte isoform, aP2, plays an important role in obesity and glucose metabolism. Recently, this protein has been detected in macrophages where it strongly contributes to the development of atherosclerosis. Here, we investigated the role of aP2 in macrophage biology and the molecular mechanisms underlying its actions. We demonstrate that aP2-deficient macrophages display defects in cholesterol accumulation and alterations in pro-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(181 citation statements)
references
References 51 publications
7
166
0
Order By: Relevance
“…Macrophages deficient in aP-2 display enhanced free fatty acids, reduced IKK and NF-B activation, and suppression of inflammatory activities (40). It is likely that free fatty acids and their derivatives generated by LPL catalytic activity may inhibit I-B degradation and NF-B activation in HAECs.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages deficient in aP-2 display enhanced free fatty acids, reduced IKK and NF-B activation, and suppression of inflammatory activities (40). It is likely that free fatty acids and their derivatives generated by LPL catalytic activity may inhibit I-B degradation and NF-B activation in HAECs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, results obtained from experimental models demonstrated that FABPs integrate metabolic and immune responses and link the inflammatory and lipid-mediated pathways that are critical in metabolic syndrome (9). In particular, the adipocyte͞macrophage FABP isoform, aP2, when deleted in mice demonstrates three major phenotypes: moderately reduced triglyceride levels, protection against type 2 diabetes when the animals were made obese, and reduced atherosclerosis despite hypercholesterolemia (6,18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both isoforms are expressed at similar levels in activated macrophages (6) and regulated by a variety of inf lammatory and metabolic mediators (8,9). The precise physiological role of these small proteins has been recognized only upon the development of genetic models to examine their function in mice (4,10,11).…”
mentioning
confidence: 99%
“…Similar to adipocytes, FABP4 expression is also induced during differentiation from monocytes to macrophages, and its expression in these cells is regulated by a wide range of proinflammatory stimuli (Pelton et al 1999, Fu et al 2000, Makowski et al 2001, Fu et al 2002, Kazemi et al 2005. In macrophages, FABP4 increases the accumulation of cholesterol ester and induces foam cell formation as well as inflammatory responses through the activation of the IKK-NF-κB and JNK-AP-1 pathways (Makowski et al 2005, Hui et al 2010). FABP4 expression is controlled at the transcriptional level by CEBP (CCAAT/enhancer-binding protein) (Christy et al 1989) and PPARγ (peroxisome proliferator-activated receptor γ) (Kletzien et al 1992, Cabre et al 2007.…”
Section: Fatty Acid-binding Proteinmentioning
confidence: 99%